Pendampingan dan Pengenalan Peluang Penelitan di Bidang Optimasi bagi Mahasiswa Matematika di Indonesia (Neolectura, 2021)
The pandemic situation has resulted in many obstacles in the lecture and research process. At the university level, online learning still faces many obstacles. Online meetings cannot replace face-to-face meetings. On the other side, students need direct interaction and communication with lecturers and fellow students. This interaction is needed in solving the subject matter and research problems. The confusion of undergraduate level students in finding ideas for final project research is quite high. Students in the third semester should have obtained the research idea to decide on their field of interest and elective courses to be taken for the next semester. This mentoring activity needs to be held as the introduction of research opportunities in Optimization. Optimization is one of the areas of interest in Mathematics that has many applications and research opportunities. Our team carried out mentoring activities and introduced research opportunities in Optimization to Mathematics students in Indonesia using the Zoom platform. The activity consists of two stages, namely the introduction and delivery of research opportunities. The activity results are expected to increase students' insight into research ideas and opportunities to complete their studies on time, even if possible faster than the specified time.